Hydrodynamic approach to boost invariant free streaming - Calzetta, Esteban Adolfo (2015)
We consider a family of exact boost invariant solutions of the transport equation for free streaming massless particles, where the one particle distribution function is defined in terms of a function of a single variable. The evolution of second and third moments of the one particle distribution function (the second moment being the energy momentum tensor (EMT) and the third moment the non equilibrium current (NEC)) depends only on two moments of that function. Given those two moments we show how to build a non linear hydrodynamic theory which reproduces the early time evolution of the EMT and the NEC. The structure of these theories may give insight on nonlinear hydrodynamic phenomena on short time scales.